THE IMPACT OF SOCIAL MEDIA ON STUDENT COMMUNICATION SKILLS - Khasanova Maftuna Ikhtiyorovna; Abduazizova Marjonaoy Akhmadjonovna (Research Focus International Scientific Journal, 2025)
Social media has transformed student communication, influencing language use, interaction styles, and engagement. This paper examines how social platforms impact students’ cognitive, social, and emotional communication skills. It highlights the advantages and challenges of social media in education, comparing digital and traditional communication methods. Understanding these effects can help educators optimize social media use to enhance communication skills.